The impact of simultaneous inoculation with Torulaspora delbrueckii and Hanseniaspora uvarum combined with Saccharomyces cerevisiae on chemical and sensory quality of Sauvignon blanc wines - Li, Linbo; Yuan, Chenyang; Zhang, Lei; Chu, Ruichao; Yu, Qingquan; Cai, Jian; Yang, Tianyou; Zhang, Mingxia (Frontiers in Microbiology, 2024)
Non-Saccharomyces yeasts have great potential in improving wine quality, showing personality characteristics, and highlighting terroir of wine. In this study, we evaluated the impact of simultaneous inoculation with the non-Saccharomyces yeasts Torulaspora delbrueckii or (and) Hanseniaspora uvarum in combination with Saccharomyces cerevisiae (EC1118 or VL3) on the aromatic compounds and sensory quality of Sauvignon blanc wines. The growth of yeast groups in the alcoholic fermentation process was tracked by using fluorescence in situ hybridization. The presence of non-Saccharomyces yeast notably impacted the distribution of S. cerevisiae and was related to the species of yeast. The co-fermentation of H. uvarum and S. cerevisiae improved the content of total ester, especially acetate esters. Simultaneous inoculation of T. delbrueckii or (and) H. uvarum significantly increased the content of total terpenes, especially linalool. Similar results were found for some higher alcohols and organic acids. Sensory evaluation showed that the wines mixed fermentation with H. uvarum owned significantly tropical fruit aroma characteristic. Citrus and mineral notes, typical aroma characteristics of Sauvignon blanc wine, were enhanced by mixed fermentation strategies with T. delbrueckii or (and) H. uvarum and different S. cerevisiae. Hence, cofermentation by T. delbrueckii or H. uvarum combined with S. cerevisiae could improve the sensory quality of Sauvignon blanc wine notably.